DONGENG DAPAT MEMBENTUK KARAKTER ANAK MENUJU BUDI PEKERTI YANG LUHUR - Fitriani, Wahyu (Jurnal Review Pendidikan dan Pengajaran, 2019)
This study aims to describe the benefits of fairy tales in formation child character. This study aims to determine the character formation of children through fairy tales and also the benefits of fairy tales in the formation of children's character. Fairy tales are stories that contain moral and social values that are useful for shaping children's character. Formation of children's character can be done in the school learning environment and home or family environment. The strategy of forming a child's character is done by giving examples, habituating to reading fables, habitual listening to tales, and creating a supportive reading environment. Storytelling is a creative activity of a teacher to convey messages to students, because elementary students cannot understand the pure advice given. They need learning that is not patronizing, so that it creates a cheerful and pleasant atmosphere. Storytelling becomes successful when students can focus on paying attention to the contents of the story and getting to know the characters that are told, then students remember the contents of the story and store it in the memory of the brain which can be taken back when needed. Furthermore, students translate the memory of stories that exist in their brains in the form of behavior that shows positive character and national cultural values.